Advancing specificity in delirium: the delirium subtyping initiative - Bowman, EML; Brummel, NE; Caplan, GA; Cunningham, C; Evered, LA; Fiest, KM; Girard, TD; Jackson, TA; LaHue, SC; Lindroth, HL; Maclullich, AMJ; McAuley, DF; et al. (Wiley, 2023)
Background Delirium, a common syndrome with heterogeneous etiologies and clinical presentations, is associated with poor long-term outcomes. Recording and analyzing all delirium equally could be hindering the field's understanding of pathophysiology and identification of targeted treatments. Current delirium subtyping methods reflect clinically evident features but likely do not account for underlying biology. Methods The delirium subtyping initiative (DSI) held three sessions with an international panel of 25 experts. Results Meeting participants suggest further characterization of delirium features to complement the existing diagnostic and statistical manual of mental disorders fifth edition text revision diagnostic criteria. These should span the range of delirium-spectrum syndromes and be measured consistently across studies. Clinical features should be recorded in conjunction with biospecimen collection, where feasible, in a standardized way, to determine temporal associations of biology coincident with clinical fluctuations. Discussion The DSI made recommendations spanning the breadth of delirium research including clinical features, study planning, data collection, and data analysis for characterization of candidate delirium subtypes.